An Analysis of Morphosemantics Process on Live TikTok Online Shop - Fitri, Azzahra Allya; Rosita, Nur (English Language and Literature, 2024)
This research aims to classify word formation processes of thrift terms, identify the types of semantic change, find out the type of contextual meaning found in TikTok live online shop Thrift Can Be Fun account. This research used descriptive qualitative method. This research used the theories of Kridalaksana (2007) for word formation process, Chaer (2013) for semantic change and Pateda (2010) for contextual meaning. The results found that there are five types of word formation process, namely affixation, reduplication, conversion, composition, shortening. Then, there are two types of semantic change also found, namely widening and totally changed. Contextual meaning found two types namely, context of situation, context of purpose and context of object. Conversion was the most word formation process types of thrift terms words that found in Thrift Can Be Fun account’s TikTok live online shop. The most dominant semantic change types found is totally changed. Then, context of object was the most contextual meaning types that found in Thrift Can Be Fun account’s TikTok live online shop.